1971
DOI: 10.1017/s0014479700023292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Moisture Stress on Two Varieties of Upland Cotton in Israel. III. The Bet-She'an Valley

Abstract: SUMMARYThe effects of moisture stress during various stages of the development of two varieties of upland cotton (Acala 4–42 and Deltapine Smoothleaf) were studied in two irrigation experiments in the Bet-She'an valley, where summer temperatures were high and evapotranspiration in the fully irrigated treatments was up to 8–10 mm./day in July and August. Optimum time for first irrigation in the Bet-She'an valley was two or three weeks before flowering and six or seven irrigations, if timed to prevent moisture s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
1

Year Published

1973
1973
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
1
0
0
1
Order By: Relevance
“…Withholding irrigation for 2 weeks resulted in a higher percentage of short fibers and a lower micronaire. Similar results were obtained with sprinkle irrigation under various soil water regimes (Amir and Bielorai 1969;Marani and Amirav 1971). Fiber elongation and strength are slightly influenced by water status while fiber length and micronaire are decreased by severe water stress (Grimes and Kirby 1992).…”
Section: Water Use In Crop Production 236supporting
confidence: 70%
“…Withholding irrigation for 2 weeks resulted in a higher percentage of short fibers and a lower micronaire. Similar results were obtained with sprinkle irrigation under various soil water regimes (Amir and Bielorai 1969;Marani and Amirav 1971). Fiber elongation and strength are slightly influenced by water status while fiber length and micronaire are decreased by severe water stress (Grimes and Kirby 1992).…”
Section: Water Use In Crop Production 236supporting
confidence: 70%
“…Under deficit irrigation regimes, Mert (2005) reported that water stress positively affected fiber fineness in his study, while Basal et al (2009) and Price (2009) reported that water stress negatively affected fiber fineness in their related studies, similar to our study. According to most of the previous studies, fiber length shortens with increasing water stress levels ( Marani, 1973 ; McWilliams, 2003 ; Pettigrew, 2004 ; Mert, 2005 ; Basal et al, 2009 ; Price, 2009 ; Rai, 2011 ; Hussein, Janat & Yakoub, 2011 ; Karademir, Karademir & Gençer, 2011 ; Cave, 2013 ). Fiber length is the fiber quality trait that is most affected by water stress.…”
Section: Discussionmentioning
confidence: 89%
“…According to Marani &Amirav (1971) , Marani (1973) , Mert (2005) and Başal et al (2009), boll weight decreases when cotton is exposed to water deficit conditions. However, Pettigrew (2004) found that water stress did not have a significant effect on the weight of an individual boll.…”
Section: Discussionmentioning
confidence: 99%
“…Çiçeklenme döneminde su kıtlığının oluşması lif uzunluğunu değiştirmemiştir. Ancak, kuraklık çiçeklenme döneminden sonra meydana geldiğinde, lif uzunluğunda azalma gözlenmiştir [10,21,22].…”
Section: Introductionunclassified